Integrating scenario planning and design thinking: Learnings from the 2014 Oxford Futures Forum. (November 2015) - Chermack, Thomas J.; Coons, Laura M.
Highlights: We summarize the article in this Special Issue on Scenarios & Design. We synthesize the core implications for practice from each article. We connect this innovative thinking to the sustainability of human existence. We make a call for increase innovation in the application of scenario planning and design thinking. Abstract: This issue of Futures has covered a lot of ground and much of it breaks new ground. It is not too bold to write that these articles have added new thinking to the scenario and design literatures. Even bolder, we believe that human existence and long-term sustainability are predicated in part on the ideas in this issue of Futures. In his recent book The Meaning of Human Existence, Pulitzer Prize winning Biologist E.O. Wilson wrote: premier among the consequences [of human existence] is the capacity to imagine possible futures, and to plan and choose among them. How wisely we use this uniquely human ability depends on the accuracy of our self-understanding. The question of greatest relevant interest is how and why we are the way we are, and from that, the meaning of our many competing visions of the future. Wilson, 2014, p. 14.